Association of Antenatal Depression with Adverse Consequences for the Mother and Newborn in Rural Ghana: Findings from the DON Population-Based Cohort Study - Weobong, Benedict (PLoS One, 2014)
BACKGROUND: Whilst there is compelling evidence of an almost 2-fold increased risk of still births, and suggestive evidence of increased mortality among offspring of mothers with psychotic disorders, only three studies have addressed the role of antenatal depression (AND) on survival of the baby. We examined these associations in a large cohort of pregnant women in Ghana. METHODS: A Cohort study nested within 4-weekly surveillance of all women of reproductive age to identify pregnancies and collect data on births and deaths in the Kintampo Health Research Centre study area of Ghana. Women were screened for AND using the Patient Health Questionnaire (PHQ-9) to ascertain DSM-IV major or minor depression. Outcomes were adverse birth outcomes, maternal/infant morbidity, and uptake of key newborn care practices, examined using logistic regression; effect sizes reported as relative risks with 95% confidence intervals. RESULTS: 20679 (89.6%) pregnant women completed the PHQ-9. The prevalence of AND was 9.9% (n = 2032) (95% confidence interval 9.4%–10.2%). AND was associated with: prolonged labour (RR 1.25, 95% CI 1.02–1.53); peripartum complications (RR 1.11, 95% CI 1.07–1.15);postpartum complications (RR 1.27, 96% CI 1.21–1.34); non-vaginal delivery (RR 1.19, 95% CI 1.02–1.40); newborn illness (RR 1.52, 95% CI 1.16–1.99); and bed net use during pregnancy (RR 0.93, 95% CI 0.89–0.98), but not neonatal deaths, still births, low birth weight, immediate breast feeding initiation, or exclusive breastfeeding. AND was marginally associated with preterm births (RR 1.32, 95% CI 0.98–1.76). CONCLUSION: This paper has contributed important evidence on the role of antenatal depression as a potential contributor to maternal and infant morbidity. Non-pharmacological treatments anchored on primary care delivery structures are recommended as an immediate step. We further recommend that trials are designed to assess if treating antenatal depression in conjunction with improving the quality of obstetric care results in improved maternal and newborn outcomes.